The Fishing Rights Conflict in the South China Sea between Vietnam and China - Mohammad Hazyar Arumbinang; Yordan Gunawan; Rizaldy Anggriawan (Faculty of Law, Sriwijaya University, Indonesia, 2021)
This research aims to understand and clarify the international legal perspec-tive relating to the current dispute and how they are resolved according to international law between Vietnam and China over fishing rights in the South China Sea. This paper has adopted a normative legal research with a statutory and historical approaches. The data will be analysed by using de-scriptive-analytical analysis. This paper reveals that there are two legal is-sues in the fishing rights conflict between Vietnam and China. First is the legality of the Nine-dashed Line by China to claim the disputed water. Sec-ond, the legality of unilateral fishing ban policy by China over the disputed water, which both has no legality under international law. Although China claims over SCS using Nine-dashed Line and unilateral fishing ban policy under international law has no legal basis, the dispute over SCS including fishing rights continued until today. The solutions offered to solve these problems include a resolution on SCS dispute must be made legally and di-plomacy to build confidence-building measures. Ideally, both states should honour the accepted negotiation steps to agree upon compensation for the effects of the disputes and be sincere and earnest in their attempts and com-mitment to resolving their dispute.